Virtual Walking Sensation by Prerecorded Oscillating Optic Flow and Synchronous Foot Vibration. (October 2019) - Kitazaki, Michiteru; Hamada, Takeo; Yoshiho, Katsuya; Kondo, Ryota; Amemiya, Tomohiro; Hirota, Koichi; Ikei, Yasushi
This article reports the first psychological evidence that the combination of oscillating optic flow and synchronous foot vibration evokes a walking sensation. In this study, we first captured a walker's first-person-view scenes with footstep timings. Participants observed the naturally oscillating scenes on a head-mounted display with vibrations on their feet and rated walking-related sensations using a Visual Analogue Scale. They perceived stronger sensations of self-motion, walking, leg action, and telepresence from the oscillating visual flow with foot vibrations than with randomized-timing vibrations or without vibrations. The artificial delay of foot vibrations with respect to the scenes diminished the walking-related sensations. These results suggest that the oscillating visual scenes and synchronous foot vibrations are effective for creating virtual walking sensations.